NATURE OF ACTIVITY FORMULATION MIXTURE OF IPA GLYPHOSATE + METSULFURON METHYL TO Cyperus rotundus WEED - ., andri; ., sarbino (Fakultas Pertanian Universitas Tanjungpura, 2020)
The use of a single herbicide is often unsatisfactory in the field. Mixing herbicides is expected to provide better control results. The purpose of this study was determine the nature of the activity formulation mixture of IPA glyphosate + methsulfuron methyl with two ratios of 24:1 and 36:1 against Cyperus rotundus weeds. The study was conducted in Experimental Field, Faculty of agriculture, Tanjungpura University, Pontianak, from January to March 2019. The research was arranged according to a Randomized Block Design. Data analysis using probit analysis continued with combination indeks calculation. The results showed that the combination index of IPA glyphosate + methulfuron methyl 24:1and 36:1 was 0,88 and 0,77 so that the two mixed herbicides were not antagonistic to C. rotundus.